La escritura creativa y su influencia en la escucha y la producción textual de las estudiantes del grado cuarto del Colegio Eucarístico de la Milagrosa (2020)
Human relationships are fundamentally based on communication, hence the need to develop in the school -and outside-the communicative skills of children and young people.In the case of the school, the strategies promoted by teachers related to speaking, listening, reading and writing are abundant and varied, which must be the object of permanent inquiry to understand and optimize all these processes.As expressed, the present study was intended as the main purpose of analyzing the influence of creative writing on the listening and textual production offourth grade students from ColegioEucarísticodelaMilagrosa(Medellín).Mixedinvestigationapproach, was supported to obtain the data in semi-structured interviews and workshops in which the 38 students and 4 teachers (of the Spanish language and other subjects) participated as informative subjects.Among the results it is emphasized that both students and teachers are aware of the importance and necessity of creative writing in processes of listening and textual production, in addition, they manifest a positive willingness to participate in activities of this type.In the case of students, they face the usual difficulties of the task of writing (especially in the formal aspects) but manifest great creativity; teachers develop various strategies that should be better systematized.It is concluded that promoting creative writing positively influences listening and textual production,but the understanding of these processes must continue to deepen.